Telessaúde na pandemia covid-19 e a saúde do trabalhador - Peixoto, Magda Helena (2024)
This research refers to the equivalent work of a master's dissertation in the Postgraduate Program in Environmental Health and Workers' Health, addresses the use of Telemedicine and aimed to understand the repercussions of Telehealth on Workers' Health, in the municipality of Uberlândia, with telehealth workers and with a patient who was accompanied by the service, using a sociodemographic questionnaire and a semi-structured interview script. The descriptive analysis of the data used Excel and the interpretation of the qualitative data was based on thematic content. This study was approved by the Ethics Committee of the Federal University of Uberlândia. Two articles were produced. The first, submitted to the Cadernos de Saúde Pública journal, involved 13 workers, 77% of whom were female, with an age range of 22 to 67 years and a standard deviation of ±16.84. With regard to the professional categories in Telehealth, 44.4% were psychologists. Regarding the workers' perspectives, it was noted that the technology can be expanded beyond pandemic monitoring. The second article involved a patient who was not hospitalized during the Covid-19 infection and was teleassisted for 14 days. The analysis allowed the reports to be categorized into two nuclei of meaning: “The impacts of telehealthcare on health” and “Strategies for expanding telehealthcare”. Telehealth is capable of strengthening ties and